Comparison of torque ripple minimization control techniques in Surface-Mounted Permanent Magnet Synchronous Machines - Peng Zhang; Sizov, G. Y.; Demerdash, N. A. O. (2011 IEEE International Electric Machines and Drives Conference, 2011)
In this paper, three calculation methods of torque for Surface-Mounted Permanent Magnet Synchronous Machines (SPMSMs) are performed, and the results including the average torque and the torque ripple from each method are compared. This is in order to enable one to choose an effective torque estimation technique for further torque ripple minimization in these machines. Accordingly, a vector controlled motor-drive model, including torque ripple minimization techniques, was developed. In this paper, a current harmonics injection and an adaptive internal model algorithm were developed for the torque ripple minimization in the vector control drive system. The corresponding simulation results are given and compared in this paper. An equivalent circuit model coupled to a Time-Stepping Finite Element (TSFE) model of the motor-drive system built in Ansoft-Maxwell V14.0 was developed to verify the above mentioned torque ripple minimization control techniques, which reduce the torque pulsations as well as eliminate the need for skewing the stator windings or the rotor permanent magnet (PM) mounts in SPMSMs.